1998
DOI: 10.1177/002215549804601205
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Scanning Microspectrofluorometry Reveals Specific Anthracyline Accumulation in Cytoplasmic Organelles of Multidrug-resistant Cancer Cells

Abstract: We used confocal microspectrofluorometry to investigate intracellular distribution of pirarubicin or THP-DOX in parental K562, CEM, and LR73 tumor cells and their corresponding multidrug-resistant (MDR) strains. Each spectrum of a recorded image was considered as a combination of cell autofluorescence and fluorescence of the drug. In the cytoplasm of parental K562, CEM, and LR73 cells, THP-DOX fluorescence emission profile was similar to that of free drug in aqueous buffer. The (I550nm/I600nm) ratio was 0. 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Applying these advantages, some groups have examined the sub-cellular distribution of anthracycline derivatives, such as ADR (DOX) and MX2, in vitro and/or in vivo using CLSM [28][29][30] . Kabuto et al 31 examined the sub-cellular distribution of MX2 in a rat glioma model and reported that CLSM was useful for the study of the cellular pharmacokinetics of anti-tumour agents.…”
Section: Discussionmentioning
confidence: 99%
“…Applying these advantages, some groups have examined the sub-cellular distribution of anthracycline derivatives, such as ADR (DOX) and MX2, in vitro and/or in vivo using CLSM [28][29][30] . Kabuto et al 31 examined the sub-cellular distribution of MX2 in a rat glioma model and reported that CLSM was useful for the study of the cellular pharmacokinetics of anti-tumour agents.…”
Section: Discussionmentioning
confidence: 99%
“…In another study it was shown, using microspectrofluorometry, that the anthracycline antibiotic pirarubicin accumulates in the Golgi body of drug resistant K562, CEM and LR73 cells. It was proposed that this accumulation occurred as a result of the Golgi body being more acidic in MDR cells and hence possessing a stronger pH gradient across its membrane that influenced the passive diffusion of the compound (Belhoussine et al, 1998). The importance of pH gradients in the vesicular sequestration of the anthracycline antibiotics was again reported in 2003 by Ouar et al In this study pH gradients were abolished in resistant cells using concanamycin A, an inhibitor of the vacuolar proton pumps that are responsible for the maintenance of pH.…”
Section: Drug Sequestration Through the Endosomal Pathwaysmentioning
confidence: 99%
“…BFA, a potent disrupter of Golgi, functions due to its inhibition of Arf1, which is vital for formation of transport vesicles originating at the TGN (Klausner et al, 1992). It has previously been shown that small molecules may be taken up into Golgi apparatus (Belhoussine et al, 1998) and it is well established that nuclear waste is often removed via the ER and sorted in the TGN before being transported to vesicles of the membrane trafficking system for degradation. With this in mind Golgi function was disrupted by BFA in order to establish the influence this organelle plays in AS-DACA's sequestration by the membrane trafficking system.…”
Section: Disrupting the Membrane Trafficking System: Influence Of Brementioning
confidence: 99%
“…Indeed, 30–40% of patients with breast or urothelial cancer treated with either doxorubicin or a combination of methotrexate, vinblastine, doxorubicin and cisplatin (MVAC) develop MDR 17. Furthermore fluorescence properties of anthracycline-like molecules such as doxorubicin have been used to study cellular uptake and distribution in sensitive and resistant living cancer cell lines including lung,18–20 melanoma,21 breast,22 urothelial,23–28 leukemia29 30 and colon 31…”
Section: Introductionmentioning
confidence: 99%